Dietary Supplement Intake is Differed by Covid-19 Risk Perception and Media Exposure among Indonesian Social Media Users - Imas Arumsari; Elia Nur Ayunin; Izza Surayya; Mega Puspa Sari (Universitas STRADA Indonesia, 2021)
Indonesian government implemented large scale social distancing with the limitation of major public activities, except vital sectors, to control the transmission of Covid-19 since its first case on March 2020. The new normal period forced people to be ready for taking individual measures to protect themselves from the virus transmission, such as washing hands, wearing mask, avoid crowds, or even taking nutrient supplement to improve their immune system. This study aims to investigate the role of media and Covid-19 risk perception on driving the supplement intake. An online survey based on social media (WhatsApp, Instagram, Facebook, and Twitter) was completed by 715 participants on June 2020. The results showed that the supplement intake was differed by age, educational background, occupation, nutritional status, Covid-19 risk perception, television, and social media news (p-value < 0.05). In conclusion, dietary supplement intake is driven by risk perception on Covid-19.